Analisis Kualitas Pelayanan Light Rail Transit (Lrt) Di Pegangsaan Dua – Velodrome - Reina Mayang Dhenarisa; Adelio Shatara Nugraha; Alphonsus Christian Gavrie; Siti Sahara (Lembaga Pengembangan Kinerja Dosen, 2023)
The quality of Light Rail Transit (LRT) services in Pegangsaan Dua - Velodrome is the result of efforts by the Jakarta Provincial Government and LRT Jakarta to improve public transportation services in Jakarta. The development of LRT Jakarta began with the increasing demand from the community for safe, comfortable, and efficient transportation access. In the process of developing LRT, a service quality analysis is carried out to determine the extent to which LRT can meet the needs of the community and measure user satisfaction levels. This analysis is carried out using various methods such as user satisfaction surveys, direct observation, and analysis of LRT usage data. From the results of this analysis, it is expected that solutions can be found to improve the quality of LRT services so that they can meet the increasing needs and satisfaction of users.